Liquid crystal alignment induced by controllable surface wettability of BiFeO3 bumps thin layer. Issue 3 (19th February 2016) - Liu, Yang; Liu, Kaihua; Wen, Pushan; Oh, Byeong-Yun; Park, Hong-Gyu; Seo, Dae-Shik
ABSTRACT: The alignment of liquid crystals (LCs) in LC-based optical devices determines the visual quality of devices, and a simple pretreatment is necessary for LC alignment. Here, we present a BiFeO3 (BFO) thin layer working as an alignment layer, homogeneously aligning LCs after a pre-thermal annealing treatment. Dramatic BFO bumps were observed during the thermal annealing process, and a corresponding enhancement in wettability was detected from measurement of tunable contact angles. LCs in the BFO bump thin layer sandwiched TN cell were found to be perfectly homogeneously aligned due to the enhanced anisotropy and wettability caused by the morphology change of the thin layer. GRAPHICAL ABSTRACT: